Penerapan Video Pembelajaran Daring Anak Usia Dini pada Masa Pandemi Covid-19 - Wahyuni Wahyuni; Rita Aryani (CV. Syntax Corporation Indonesia, 2021)
Learning media is one of the important factors in learning activities. The media becomes an intermediary between educators and students in the delivery of learning materials. The outbreak of the COVID-19 pandemic in Indonesia has had a significant impact on Indonesian education. One of the learning media that is an alternative choice for educators during the COVID-19 pandemic is the use of learning video media. This study aims to discuss and review the learning media used in early childhood learning online which are used as learning media at PAUD Sahabat Dhika Gunung Sindur Bogor during the COVID-19 pandemic. This study uses a qualitative research type, namely using analysis in a special natural context by describing what learning media is used and its application in PAUD Sahabat Dhika Gunung-Sindur Bogor. Online learning at PAUD Sahabat Dhika uses several stages, namely initial planning, preparation, storage. , use, development, evaluation of learning media and also explain the application of the content of online learning videos. So it can be concluded that online learning videos containing the results of teacher videos are taken from classroom teaching activities made by the teacher council in turn and then given via Whatsappgroup. While the content of the learning videos related to the material presented by the teacher to students is carried out in detail and detail so that students and parents can understand the material activities conveyed by the teacher through the video. The results of this study show that the implementation of learning during the Covid-19 pandemic using learning video media in Early Childhood Education is going well. Learning video media is effective during the Covid-19 pandemic, because it makes it easier for educators to teach material and makes it easier for students to understand learning material.